A Prisoner of His Own Creative Imagination: A Decolonial Discourse with David Bosch’s Missional View of a Church as an Alternative Community - Mashau, Thinandavha Derrick (Ecclesial Futures, 2020)
David Bosch’s ecclesiology remains one of the most influential in missiological circles globally. This article sought to interrogate Bosch’s creative imagination, with particular reference to his missional ecclesiology and in particular his view on the church as an alternative community from a decolonial perspective. What prompted this study is the ambiguity and at times, contradictory posture or even what seems to be a betrayal of Bosch’s thought in comparison with his praxis. This article discovered that Bosch was not just a prisoner of his creative imagination, but also a prisoner of his faith, his views on truth, unity of the church, transformation, violence and reconciliation and of hope.